RANCANG BANGUN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ARTICULATE STORYLINE PADA MATA PELAJARAN IPA MATERI BUMI DAN TATA SURYA KELAS VII SMP NEGERI 17 SURAKARTA TAHUN PELAJARAN 2024/2025 - Rachmad Indriastama; Hera Heru Sri Suryanti; Moenawar Kholil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The study aims to describe the feasibility and effectiveness of interactive science learning media based on Articulate Storyline. The method used is Research and Development (R&D) with the ADDIE development model. Data collection technique use validation sheet analysis of material experts, media experts and sains teachers. Analysis relied on the Likert scale for media fasibility score and blackbox testing. The result of the study show that interactive science learning media based on Articulate Storyline obtained a material validity score of 92% with very feasible criteria, then media validity of 90% with very feasible criteria and teacher validity score of 85,33% with very feasible criteria. Based on the results of the study, it was concluded that interactive science learning media based on Articulate Storyline on the Earth and Solar System material as a whole met the criteria of being feasible and effective.